Evaluation of environmental and economic effectiveness of the Cross Compliance 4.3 Standard ‘Maintenance of olive groves and vineyards in good vegetative conditions’ - Sansone, Luigi; Carroni, Antonio Melchiorre; Fedrizzi, Marco; Santilli, Elena; Pipitone, Giuseppina; Pagano, Mauro; Sperandio, Giulio; Guerrieri, Mirko; Puri, Daniele; Zaffina, Francesco; Salis, Mauro; Ruda, Paola; et al. (Italian Journal of Agronomy, 2015)
This paper reports the first observations made in three farms of the Council for Agricultural Research and Economics (CREA) relating to the environmental monitoring of the Standard 4.3 'Maintenance of olive groves and vineyards in good vegetative conditions' and analysis of differential of competitiveness for both crops.